Long-Term Dynamics of Coxiella burnetii in Farmed Red Deer (Cervus elaphus) - González-Barrio, David; Fernández-de-Mera, Isabel G.; Ortiz, José Antonio; Queirós, João; Ruiz-Fons, Francisco (Frontiers in Veterinary Science, 2015)
Several aspects of the dynamics of Coxiella burnetii that are relevant for the implementation of control strategies in ruminant herds with endemic Q-fever are unknown. We designed a longitudinal study to monitor the dynamics of exposure to C. burnetii in a red deer herd with endemic infection in order to allow the design of Q fever specific control approaches. Other relevant aspects of the dynamics of C. burnetii - the effect of herd immune status, age, season and early infection on exposure, the average half-life of antibodies, the presence and duration of maternal humoral immunity and the age of first exposure - were analysed. The dynamics of C. burnetii in deer herds seems to be modulated by host herd and host individual factors and by particular host life history traits. Red deer females become exposed to C. burnetii at the beginning of their second year since maternal antibodies protect them after birth and during the main pathogen shedding season - at the end of spring-early summer. Infection pressure varies between years, probably associated to herd immunity effects, determining inter-annual variation in the risk of exposure. These results suggest that any strategy applied to control C. burnetii in deer herds should be designed to induce immunity in their first year of life immediately after losing maternal antibodies. The short average life of C. burnetii antibodies suggests that any protection based upon humoral immunity would require re-vaccination every 6 months.